Subjective Well-Being in Healthcare Professionals in Colombia: On the Constitution of Subjectivity and the Ethics of Care in Times of the COVID-19 Pandemic - Barragán-Giraldo, Diego Fernando; Anzola-Pardo, Giovanni; Guerrero-Lucero, Maura Andrea (Frontiers in Psychology, 2021)
The purpose of this work is to reveal how subjective well-being has been generated in a group of professionals in the healthcare field in Colombia, who carried out postgraduate studies at the time of the pandemic caused by the novel SARS-CoV-2 coronavirus in a synchronous and remote learning course facilitated by employing digital technologies. In methodological terms, two moments were assumed, one qualitative, taking into account some elements of narrative research and discourse analysis; and another quantitative through a rapid reconnaissance survey. The research assumes the constitution of subjectivity from memory and everyday life, as well as the ethics of care concerning caring for oneself and others, as categories that were (re)signified with the narratives —and as notions that make up the theoretical corpus— to understand the subjective well-being.